Tetrahydroanthracene Derivative: Anti-microbial Isolate from Acanthospermum hispidum DC - Olawumi, Olajide; Ibrahim, Oladosu; Christianah, Fakunle (International Journal of Advanced Chemistry, 2014)
The leaves and stems of Acanthospermum hispidium were extracted with distilled ethanol using cold extraction and concentrated using a rotary evaporator at 37 0C. The crude extract was partitioned successively using hexane, benzene and methanol. Fractions 19, 20 and 21 purified on Sephadex LH-20 gave a compound elucidated to be 1, 3, 6, 8-tetrahydroxyl-9-anthracene carbonaldehyde, using the state-of-art tools of spectrometry. The results of the antimicrobial test on the isolated compound show activity against P. mirabilis, B. subtilis, P. aeruginosa, C. albican, S. typhi and B. cereus at minimum inhibitory concentration (MIC) value of 100ppm. Keywords: Acanthospermum hispidum, Anthracene Carbonaldehyde, Antimicrobial Test, Minimum Inhibitory Concentration.